OBSERVATION ON THE USE OF AUDIOVISUAL MEDIA IN HELMINTHIASIS PREVENTION EDUCATION TO ELEMENTARY STUDENTS IN BLAHKIUH (Proceedings of the International Conference on Public Health, 2022)
Helminthiasis is one of the parasitic diseases that infect the human intestinesdue to poor personal hygiene and sanitation which mostly occurs in children and affectstheir development and performance. The use of audio-visual media to educate the childrenat risk should help the transfer of knowledge with simpler information and more attractiveapproach. This study aims to obtain the insight of responses from elementary schoolstudents as the target audience in absorbing the information about Helminthiasisprevention through audio-visual media. An observational study with a qualitative approachwas carried out at Elementary School Number 3 Blahkiuh, Abiansemal sub-district, Bali,in December 2021. 80 students from grades 1, 2, and 3 that were involved in healtheducation were directly observed. The observations utilized a checklist that assessed thestudent’s capability to mention, explain, and define the information themselves, along withexamples. Information regarding the cause, transmission, impact, and prevention ofhelminthiasis was delivered using a three minutes animated video. The observation showsthat the use of animated video in the dissemination of health information to students ingrades 1, 2, and 3 provides a good response from them in terms of their interest in the topicand media along with their active engagement in learning and receiving informationrelated to Helminthiasis prevention. Delivering information through animated video tostudents in grades 1, 2, and 3 as a group in the early stage of school provide to bebeneficial for the increasing student’s knowledge of new health information with anattractive approach.
Keywords: audio-visual; responses; helminthiasis; elementary students